FRAGMENTED LIVES: EXPLORING THE INNER WORLDS OF GIG WORKERS - Bhimavarapu, Anitha; Krishna, U M Gopal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The gig economy has become a prominent topic in the 21st century, according to an independent review of workers’ emerging era. There are many different types of occupations available in India’s gig economy, and the sum of people working in this sector continues to rise. Gig workers face various obstacles. The psychological requirements for gig workers have slowly begun to receive prominence. Limited study exists on psychological capital among gig workers in India. This study intended to test a "Psychological Capital Questionnaire (PCQ)" for freelance employees. The 24-item PCQ measured "self-efficacy, optimism, hope, and resilience. PsyCap can help individuals behave safely, reduce job expectations, and improve safety leadership. We used survey methods to get the data, with 149 samples participating as respondents. The study found that the PCQ dimension in India has strong psychometric qualities, making it a suitable tool for assessing psychological capital in Indian gig employees.